Reservoir simulation for enhanced gas recovery: An economic evaluation - Hussen, Chawarwan; Amin, Robert; Madden, Gary; Evans, Brian (Elsevier Inc., 2012)
The economic aspects of injecting carbon dioxide (CO2) into natural gas reservoirs for geo-sequestration and enhance natural gas production is investigated using a gas reservoir as case study. This method of enhanced gas production is attractive because it enhances the rate of gas recovery and reduces anthropogenic gas emissions. This paper focuses on the recovery factor of methane achieved by supercritical CO2 (SCO2) displacement under various production scenarios. Reservoir simulation models used based on assumptions and limitations by the degree of SCO2 and methane (C1) mixing in the reservoir, and operating parameters to delay CO2 breakthrough. Additionally, the economic viability of the enhanced gas recovery (EGR) process is analyzed to optimize the CO2 injection timing and injection rates. The re-injection strategies in each reservoir simulation case were designed to minimize the risk of methane contamination in the reservoir and maintaining the minimum level of CO2 in the production gas. Optimum injection strategies for various cases are presented in this paper that includes the adjustment of CO2 re-injection rate, velocities, timing and economical model.